Therapeutic Development for CGG Repeat Expansion-Associated Neurodegeneration - Xu, Keqin; Li, Yujing; Allen, Emily G.; Jin, Peng (Frontiers in Cellular Neuroscience, 2021)
Non-coding repeat expansions, such as CGG, GGC, CUG, CCUG, and GGGGCC, have been shown to be involved in many human diseases, particularly neurological disorders. Of the diverse pathogenic mechanisms proposed in these neurodegenerative diseases, dysregulated RNA metabolism has emerged as an important contributor. Expanded repeat RNAs that form particular structures aggregate to form RNA foci, sequestering various RNA binding proteins and consequently altering RNA splicing, transport, and other downstream biological processes. One of these repeat expansion-associated diseases, fragile X-associated tremor/ataxia syndrome (FXTAS), is caused by a CGG repeat expansion in the 5’UTR region of the fragile X mental retardation 1 (FMR1) gene. Moreover, recent studies have revealed abnormal GGC repeat expansion within the 5’UTR region of the NOTCH2NLC gene in both essential tremor (ET) and neuronal intranuclear inclusion disease (NIID). These CGG repeat expansion-associated diseases share genetic, pathological, and clinical features. Identification of the similarities at the molecular level could lead to a better understanding of the disease mechanisms as well as developing novel therapeutic strategies. Here, we highlight our current understanding of the molecular pathogenesis of CGG repeat expansion-associated diseases and discuss potential therapeutic interventions for these neurological disorders.